Comparison of healthcare workers and non-healthcare workers in terms of obsessive-compulsive and depressive symptoms during COVID-19 pandemic: a longitudinal case-controlled study - Uyar, Betul; Donmezdil, Suleyman (Frontiers in Public Health, 2023)
Objective The aim of this study was to investigate the obsessive-compulsive and depressive symptoms of healthcare workers in a case-control setting as longitudinal. Method In this study included 49 healthcare workers and 47 non-health workers. A sociodemographic data form, the Maudsley Obsessive-Compulsive Inventory (MOCI), the Symptom Checklist-90 (SCL-90), and the Hamilton Depression Rating Scale (HAM-D) were used to assess individuals between June 1, 2020 and June 30, 2021. We assessed the same healthcare workers after 12 months on June 30, 2021 using MOCI, HAM-D, and SCL-90. Results MOCI and SCL-90 obsessive-compulsive subscale scores were significantly higher in the healthcare workers than in the non-health workers. When we assessed MOCI, HAM-D, and SCL-90 obsessive-compulsive subscale scores after 12 months, there was a statistically significant decrease in the scores of all three scales among the healthcare workers. Conclusion The results of the study showed that healthcare workers were more likely to have obsessive-compulsive symptoms than non-health workers in the early part of the pandemic on June 1, 2020, as shown by their scores on MOCI and the obsessive-compulsive subscale of SCL-90. When we assessed the same participants after 12 months (June 30, 2021), both MOCI and SCL-90 obsessive-compulsive subscale scores had decreased significantly. In contrast to these results, HAM-D scores significantly increased.